1988
DOI: 10.1203/00006450-198807000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Incorporation of Ingested 58-Iron by Infants

Abstract: ABSTRACT. The least abundant stable isotope of iron, "Fe (natural abundance 0.322 weight %), was administered orally to infants to explore the feasibility of using a stable rather than a radioisotope in studies of iron absorption. The dose of 58Fe was given between feedings at age 126 days. The mass isotope ratio, 58Fe/57Fe, was determined in blood by inductively coupled plasma mass spectroscopy and at ages ICPJMS, inductively coupled plasma mass spectrometry MIR, mass isotope ratio MR, measured ratioIron def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 16 publications
3
40
1
Order By: Relevance
“…In adults this is generally attributed to differenccs in Fe stores (measured by serum/ plasma ferritin concentrations). (21). However, in the present study, when the relationship between Hb incorporation (all foods fed without ascorbic acid) and plasma ferritin levels was examined (23), there was no significant correlation (Spearman r = -0.212).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In adults this is generally attributed to differenccs in Fe stores (measured by serum/ plasma ferritin concentrations). (21). However, in the present study, when the relationship between Hb incorporation (all foods fed without ascorbic acid) and plasma ferritin levels was examined (23), there was no significant correlation (Spearman r = -0.212).…”
Section: Discussionmentioning
confidence: 61%
“…There are, in fact, only Individual and geometric mean (-SD, +SD) values a few isotopic studies in which Fe absorption from foods has been detcrmined in infants, either by whole body counting (16), fecal balance (17), or Hb incorporation techniques (18). In recent years, efforts have been made to develop the methodology required to use stable instead of radioisotopes, so as to enable studies to be performed directly on infants by fecal monitoring (19) or red blood cell enrichment (10,(20)(21)(22). The present report presents results of a unique study in which two stable isotopes have been administered orally to infants, and a third one was used to quantify blood enrichment with the isotopes (bioavailability) from a small volume of capillary blood using isotope dilution mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%
“…The precision of the measurements of incorporation of stable isotopes into red blood cells can be estimated based on the uncertainties of the determination of the isotope ratios of both baseline and enriched samples (11,20). At low fractional Fe incorporation, when the measured isotope ratios are close to the detection limit, the errors increase.…”
Section: Subjectsmentioning
confidence: 99%
“…The quantity of administered 5 8~e and 5 7~e incorporated into red blood cells was calculated in a manner similar to that used by Fomon et al (20). Circulating Fe was calculated based on body weight and on the assumption of 65 mL/kg body weight (20). Furthermore, 90% of initially absorbed Fe was assumed to be incorporated into red blood cells (12)-…”
Section: Subjectsmentioning
confidence: 99%
“…Studies have suggested that hemoglobin level is a valid parameter to evaluate whether the new iron formulations have improved absorption and bioavailability. 23 Higher level of mean hemoglobin concentration in group IV and group III demonstrates that iron chelate can be considered as a preferred formulation to increase the gastrointestinal absorption and bioavailability of iron. One aspect of this impressive absorption of iron is the neutralization of this ion during the chelating process which can prevent the iron interactions with phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%